ISLAMIC CULTURAL APPROACH IN TEACHING ENGLISH - Dalmeri Dalmeri (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2010)
This paper analyzes the cultural approach in teaching English. A foreign language teacher has a responsibility to implement the cultural approaches in order to socialize the language to the learners through the culture. Consequently, students must learn culture when they learn language.In other words, the culture must be adapted by the students in order to get success in learning language.Key words: teaching English, reflects of culture, Islamic cultural approach